Inovasi Pembuatan Tong Sampah Organik dan Anorganik dari Galon Bekas Sebagai Solusi Pengelolaan Sampah di Desa Latsari Jombang Jawa Timur - Debbie Melisa Dewi; Silvia Kurnia Illahi; Calvin Maulana Dwi Rangga Putra; Roziana Febrianita (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Waste management is one of the main challenges in Latsari Village, Jombang, East Java, which has an impact on environmental cleanliness and public health. This research aims to develop innovations in making waste cans from used gallons as a practical and sustainable solution for waste management in the village. The method used involves collecting used gallons, designing functional garbage cans, and socializing to the community regarding the importance of waste sorting. The results of the study show that the waste cans from used gallons are able to increase public awareness of the importance of environmental cleanliness and reduce the volume of scattered waste. In addition, this initiative also provides added value through the use of plastic waste that was previously not used. In conclusion, this innovation is not only effective in improving waste management in Latsari Village, but also has a positive impact on the environment and society. The broader implementation of this program has the potential to be a model that can be applied in other regions with similar challenges.